HMOs and managed care in Malaysia: what can we anticipate from the experience of Singapore and the United States? - Phua, K.L., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
Managed Care Organisations (MCOs) are now part of the Malaysian medical landscape. Its proponents believe that it will shift the emphasis of medicine back to preventive and primary care, increase efficiency as well as control costs. Its detractors believe that, among other things, it will result in deterioration of quality of care. This paper discusses the experience of Singapore and the United States with managed care. It is noted that managed care has not taken off in Singapore.However, managed care is the dominant mode of organisation of healthcare services in the United States. Factors likely to affect the growth of managed care in Malaysia are discussed. Whatever its future here, useful innovations from managed care such as clinical practice guidelines, use of formularies and generic drugs etc. can possibly be adopted for Malaysia. Nevertheless, there is a need for proper regulation of Malaysian MCOs.